The Influence of Work-Life Balance and Organizational Culture on Employee Performance at a Regional Public Company - Habib Ilham; Lisa Harry Sulistiyowati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Employee performance in regional public companies is strongly shaped by work‑life balance and organizational culture, both of which are critical for sustaining productivity and service quality. This study aims to analyze the influence of work-life balance (X1) and organizational culture (X2) on employee performance (Y) at a Regional Public Company in Indramayu Regency. Using an associative quantitative approach, the researcher determined the interdependencies between the variables. The Regional Public Company recruited 108 people to take part in the study by using a stratified random selection method based on a Slovin algorithm. Following data collection using a Likert scale questionnaire, SPSS version 26 was used to perform multiple linear regression analysis. The research found that work-life balance positively impacted employee performance, with a t-value of 11.501 and a significance level of 0.000 (<0.05). The research proved that the culture of the organization significantly impacts employee performance in a good way (B = 0.093; t_value = 2.121; Sig. 0.036 < 0.05). With a mean of 69.076 and a significance level of 0.000 (less than 0.05), a good work-life balance and a supportive work environment significantly affect productivity. With an Adjusted R² value of 0.560, we can see that these two variables explain 56.0% of the variance in how well employees perform. Unrelated variables may account for the remaining 44.0%. Hence, a Regional Public Company in Indramayu Regency may promote a good work-life balance for its employees by establishing an engaging work environment.